Impact of aging on hepatic reserve after preoperative portal vein embolization in hepatectomy for perihilar cholangiocarcinoma - Shinichi Nakanuma; Takahiro Ogi; Hiroaki Sugita; Ryosuke Gabata; Tomokazu Tokoro; Ryohei Takei; Kaichiro Kato; Satoshi Takada; Mitsuyoshi Okazaki; Isamu Makino; Shintaro Yagi (Asian Journal of Surgery)
Purpose: In the current situation of an increasing older adult population with perihilar cholangiocarcinoma (PHCC), the benefits and risks of surgical treatment of PHCC in older people remain controversial. Portal vein embolization (PVE) is a useful preoperative procedure to improve hepatic reserve in the future remnant liver (FRL) and avoid postoperative liver failure after extended hepatectomy for PHCC. This study aimed to evaluate the influence of aging on PVE. Methods: We enrolled 25 patients who underwent right hepatectomy with percutaneous transhepatic PVE. Participants aged <70 years (n = 13) and ≥70 years (n = 12) were compared; correlation coefficients were evaluated using all cases. The FRL volume/total liver volume (FRLV/TLV) ratio and the indocyanine green (ICG) clearance rate (ICG-K) fraction of FRL to total liver (ICG-Krem) were analyzed as FRL hepatic reserves. Results: FRLV/TLV ratio increased after PVE in <70 years and ≥70 years groups (p = 0.002 and p = 0.013, respectively). The change in ICG-K values from before to after PVE varied between both groups (p = 0.040). The ICG-Krem value after PVE increased only in the <70 years group (p = 0.009). A review of all cases showed a negative correlation between the change (after - before PVE) in the ICG-K and ICG-Krem values and age (r = −0.4827, p = 0.0145 and r = −0.4328, p = 0.0306, respectively). Conclusions: This study showed aging suppresses hepatic reserve improvement in the FRL, particularly in ICG clearance after PVE in PHCC cases.